Missing - Hauser, Thomas; Vangelis Musiker 1943-2022; Hauser, Thomas (The Criterion Coll., 2008)
As the title screens proclaim, "This film is based on a true story. The incidents and facts are documented. Some of the names have been changed to protect the innocent and also to protect the film." In a Latin American country in the throes of a military coup, Charles Horman, an American journalist and filmmaker living there with his wife Joyce, disappears--never to be seen again. His father Ed always found his son flaky and naïve, and didn't approve of his lifestyle, but he joins Joyce in a wild-goose chase through bureaucratic dead ends. They eventually come to suspect that the American consulate is lying to them about Charles' disappearance and about their country's investment in the coup's success. Ed makes the transition from unquestioning patriot to newly awakened skeptic of U.S. covert activities, a decent citizen who embodies the conscience of a nation.
Aspect ratio 1.85:1, 16:9 widescreen. - Restored high-definition digital transfer
Orig.: USA 1982
Enth. video interviews with Costa-Gavras, Joyce Horman (wife of Charles Horman), producers Edward and Mildred Lewis and Sean Daniel, and Thomas Hauser, author of "The Execution of Charles Horman", the film's source ; video interviews from the 1982 Cannes Film Festival with Costa-Gavras, Jack Lemmon, Ed Horman (father of Charles), and Joyce Horman ; video interview with Peter Kornbluh, author of "The Pinochet file", examining declassified documents concerning the 1973 military coup in Chile and the case of Charles Horman ; highlights from the 2002 Charles Horman Truth Project event honoring "Missing", with actors Sissy Spacek, John Shea, and Melanie Mayron, among others ; a booklet featuring a new essay by critic Michael Wood, an open letter from Horman family friend Terry Simon, an interview with Costa-Gavras, and the U.S. State Department's official response to "Missing"
Keywords: Hauser, Thomas -- Film and video adaptations; Horman, Charles <1942-1973> -- Drama; Geschichte 1900-2000; Außenpolitik; Geschichte; Politik; Coups d'état -- Drama; Disappeared persons -- Drama; Journalists -- Drama; Missing persons -- Drama; USA; Chile -- Foreign relations -- United States -- Drama; Chile -- History -- Coup d'état, 1973 -- Drama; South America -- Politics and government -- 20th century -- Drama; United States -- Foreign relations -- Drama; Detective and mystery films; Feature films; Fiction films; Political films; Video recordings for the hearing impaired; Mystery - Feature; Mystery films; Political - Feature